Healing Brain Injury with Chinese Medical Approaches : Integrative Approaches for Practitioners. - Wingate, Douglas S. (Jessica Kingsley Publishers, 2018)
This extensive clinical guide to treating minor and acute brain injury offers clear instruction for acupuncturists and other Chinese medicine practitioners. It explains how symptoms such as headache, dizziness and anxiety relate to brain injury, and differences in approaches to treatment when working with children or veterans.